Features of Epidemic Process of Influenza and its Etiology in the Countries of the Northern and Southern Hemispheres in the Period of Circulation of Pandemic Virus A(H1N1)pdm09 (According to WHO) - L. S. Karpova; M. Yu. Pelikh; N. M. Popovtseva; T. P Stolyarova; K. M. Volik (Эпидемиология и вакцинопрофилактика)
Relevance. Influenza is characterized by global distribution and the difference in its seasonality in countries with temperate and tropical climates. The importance of studying antigenic variation of influenza viruses due to the fact that changes in the antigenic structure is an evolutionary mechanism of adaptation of the virus to ensure its survival and cause annual epidemics.Aims. The Aim of this study was to identify the peculiarities of the geographical spread of influenza (seasonal), etiology and the rate of antigenic variability of influenza viruses A and B.Materials and methods. Based on data from WHO Reference research centers, information was collected on circulating influenza virus strains from 1975 A(H3N2), 1977 A(H1N1)pdm09 and type B of the Yamagata and Victoria lines from 1987 to 2019, as well as data on the number of all identified influenza viruses and individual strains circulating in the Northern and Southern hemispheres from 2008 to 2018.Results and discussion. Analysis of the global spread of influenza, its etiology and antigenic variability of viruses, according to WHO, showed that the influenza A(H1N1)pdm09 virus was the main causative agent of epidemics and regional outbreaks in seasons of high influenza activity in all countries except the United States and Canada, where influenza A(H3N2) and B viruses dominated in countries with severe seasonality, the change of season led to a change in the etiology of influenza, and in tropical countries, the A(H1N1)pdm09 virus more often remained dominant in all seasons of the year.Conclusions. The pronounced seasonality of influenza in Northern countries and its absence in tropical countries, where regional outbreaks prevailed in all seasons of the year, were confirmed. Low antigenic variability of influenza A(H1N1)pdm09 strains was confirmed, and the highest – A(H3N2). Among influenza B strains in the Victoria line had less antigenic variability, because the duration of its circulation before the appearance of a new drift variant was longer than that of the Yamagata line. The tendency to increase the total duration of circulation of influenza viruses B/Victoria, A(H1N1)pdm09 and B/Yamagata due to increased circulation before the emergence of new drift variants is shown.